Ekonomi Kreatif dan Merek - Hendrawan, Daniel (Zenit, 2015)
Indonesia have an enormous population. The population is much this cause in Indonesia there are various kinds of industrial activities to boost the economy. Industrial improved and developedquite rapidly at the moment. The industry that is eexpanding quite a lot is the creative economy. Creative economy is the development of creativity, taste and human initiative, because the creative economy is something that can improve the well-being of not a few more people who join and trailing thus requiring it differentiator. This distinction is one of them is a brand that could be a distinguishing element of a product or service.Keywords : Brand, creative economic, industry